Towards understanding the influenza virus ribonucleoprotein complex: novel structural and functional approaches - Zhu, AZ (2024)
Influenza viruses pose a significant public health concern, given their capacity to cause seasonal epidemics and pandemics like the infamous 1918 influenza pandemic. Central to the viral life cycle is a protein-RNA complex known as viral ribonucleoprotein (vRNP), for viral genome transcription and replication. For decades, studies focused on individual vRNP protein components, namely viral polymerase and nucleoprotein (NP), along with their regulators. Nevertheless, the ultimate goal of visualizing vRNP in various functional states at the molecular level and in real-time remains to be achieved. To progress toward this objective, establishing a minimal system that reconstitutes vRNP functions in a completely cell-free environment would be advantageous. Additionally, there is a need to image vRNPs at a resolution that allows unambiguous localisation of each vRNP component. During my DPhil, my aim was to make advancements toward this goal.